Kurtkrammeria tiancaiensis sp. nov. a new cymbelloid species (Bacillariophyceae) from Lijiang Laojunshan National Park in Yunnan Province, China - Zhang, Wei; Gu, Xue-Wei; Bao, Ming-Yan; Kociolek, John Patrick; Blanco, Saùl; Li, Yan-Ling (Phytotaxa, 2020)
During a survey of freshwater diatoms from a mountain lake, Lake Tiancai, Laojunshan National Park, Hengduan Mountain Range, Lijiang City, Yunnan Province, China, a new Kurtkrammeria species, Kurtkrammeria tiancaiensis sp. nov. was recorded. A detailed morphological description of K. tiancaiensis is presented, based on light and scanning electron microscopy. The main features of K. tiancaiensis include slightly dorsiventral valves with narrowly rounded, or slightly protracted ends, a wide central area, apical pore fields at both poles and lack of stigmata. The new species is compared with K. treinishii, K. weilandii, K. lacusglacialis and K. eileencoxiae (≡ Gomphonema eileencoxiae), all of which show similar valve outlines to K. tiancaiensis, but differ in details of size, striae density, puncta density, number of apical pore fields, shape of the central area and/or presence of stigmata.